2022
DOI: 10.3390/ijms23094780
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Metabolomics and Transcriptomics Reveals Molecular Mechanisms of Anthocyanin Metabolism in the Zikui Tea Plant (Camellia sinensis cv. Zikui)

Abstract: In this study, we performed an association analysis of metabolomics and transcriptomics to reveal the anthocyanin biosynthesis mechanism in a new purple-leaf tea cultivar Zikui (Camellia sinensis cv. Zikui) (ZK). Three glycosylated anthocyanins were identified, including petunidin 3-O-glucoside, cyanidin 3-O-galactoside, and cyanidin 3-O-glucoside, and their contents were the highest in ZK leaves at 15 days. This is the first report on petunidin 3-O-glucoside in purple-leaf tea. Integrated analysis of the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 44 publications
3
28
0
Order By: Relevance
“…During fruit development and coloring of Vitis vinifera , it was found that the activation of the flavonoid pathway resulting in the total flavonoid and anthocyanin accumulation had a strong correlation with the F3′H expression ( Jeong et al, 2006 ). Similar conclusions were drawn in Arabidopsis , Camellia sinensis , Sorghum bicolor , and other plants ( Forkmann and Martens, 2001 ; He et al, 2020a ; Cai et al, 2022 ; Hildreth et al, 2022 ). Interestingly, in Korean varieties of white, black, and red rice ( Oryza sativa ), 2 F3′Hs ( CYP75B3 and CYP75B4 ) showed different expression patterns.…”
Section: Discussionsupporting
confidence: 78%
“…During fruit development and coloring of Vitis vinifera , it was found that the activation of the flavonoid pathway resulting in the total flavonoid and anthocyanin accumulation had a strong correlation with the F3′H expression ( Jeong et al, 2006 ). Similar conclusions were drawn in Arabidopsis , Camellia sinensis , Sorghum bicolor , and other plants ( Forkmann and Martens, 2001 ; He et al, 2020a ; Cai et al, 2022 ; Hildreth et al, 2022 ). Interestingly, in Korean varieties of white, black, and red rice ( Oryza sativa ), 2 F3′Hs ( CYP75B3 and CYP75B4 ) showed different expression patterns.…”
Section: Discussionsupporting
confidence: 78%
“…Notably, petunidin 3- O -glucoside, which was less identified in purple leaf tea plants, was also identified. This result consistent with ‘Zikui’ purple tea cultivar [ 31 ]. Furthermore, most of anthocyanins were down-regulated in the ‘BTSC’ group ( Figure 2 ) and the total anthocyanin content was also lower than that of the ‘BTZY’ group ( Figure 3 H).…”
Section: Discussionsupporting
confidence: 88%
“…The flower color is due to the accumulation of carotenoids, flavonoids, and betalains (Sapir et al, 2021). Metabolomics is a powerful tool for analyzing the differential metabolite components and relative contents of pigments (Cai et al, 2022; Zhang et al, 2022). In this study, we found that there were large differences in the total anthocyanin content of R. glutinosa , R. chingii , and R. henryi , which were consistent with the corolla colors of the three species (Figures 1A, 2A, and S1).…”
Section: Discussionmentioning
confidence: 99%